How does social presence influence public crisis information sharing intention? Situational pressure perspective - Xiaoan Guo; Hengjiang Jin; Tianzhe Qi (Frontiers Media S.A., 2023)
ObjectivePublic crises seriously affect social stability and personal health. When individuals are in a public crisis environment, they will have the impulse and intention to share information, which is a behavioral attitude shown in the face of a crisis. Public crisis information sharing intention will be affected by many factors. This study aims to examine how the process of social presence may influence information sharing intentions during a public crisis and the mediating effects of situational pressure, including risk perception of disease infection and consistency of perception of opinion climate.MethodsThis was a cross-sectional study with 505 youth SNS users. In order to collect as suitable samples as possible, a research website was commissioned to conduct a questionnaire in the early stages of the COVID-19 pandemic in China. This questionnaire was utilized to measure social presence, risk perception of disease infection, consistency of perception of opinion climate and intention to share information about COVID-19. Structural equation modeling was used to examine variable relationships in the research model.ResultsThe results showed that social presence was significantly and positively associated with risk perception of disease infection (B = 0.42, p < 0.001), consistency of perception of opinion climate (B = 0.43, p < 0.001) and intention to share information about COVID-19 (B = 0.48, p < 0.001). Risk perception of disease infection (B = 0.19, p < 0.001) and consistency of perception of opinion climate (B = 0.18, p = 0.002) positively predicted youth SNS users' intention to share information about COVID-19. Risk perception of disease infection and consistency of perception of opinion climate mediated the relationship between social presence and intention to share information about COVID-19 (Z = 2.66, CI: 0.03, 0.15; Z = 2.66, CI: 0.02, 0.16).ConclusionThe study further deepens our understanding of the mechanisms underlying social presence and information sharing intentions. These new findings suggest that some situational cues, including media environment factors (social presence) and perceived stress factors (risk perception of disease infection, consistency of perception of opinion climate) may influence information sharing intention. From the perspective of communication psychology, this study enriched the assessment of information sharing on social media and contributes to understanding of social presence and situation pressure, and it helps to provide specific references for effectively promoting netizens' intention to share information about public crises.